The Portrayal of the Female Heroine in Ahdaf Soueif’s In the Eye of the Sun and Monica Ali’s Brick Lane: A Diasporic Analysis - Tasneem Mady; Iman Sehsah; waleed samir (International Journal of Advanced Humanities Research)
This paper explores the portrayal of female heroine in Ahdaf Soueif's In the Eye of the Sun and Monica Ali's Brick Lane through a diasporic lens. Both novels present protagonists who navigate personal, cultural, and societal challenges while living within and between multiple worlds—Egypt and England. For Soueif’s Asya, and Bangladesh and, for Ali’s Nazneen, the UK. By examining the diasporic experience of these characters, the paper highlights how displacement, migration, and identity shape the female heroines’ journey toward self-realization. The paper draws upon diaspora studies to analyze how cultural hybridity, gender expectations, and socio-political realities influence the development of the female protagonists. The analysis seeks to demonstrate how both authors challenge traditional gender roles, providing nuanced portrayals of women’s empowerment in the context of migration and cultural negotiation aiming to provide a broader understanding of concepts as identity and womanhood within the diasporic experience. Key words: Diaspora, Hybridity, Cultural Identity, Third Space.